Montenegro : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes the long-term growth prospects and the output gap in Montenegro. Historical growth in Montenegro was driven mostly by capital with some contribution from labor, while total factor productivity (TFP) contributed negatively. Going forward, in the baseline growth accounting framework with no reforms, employment will likely have a slightly negative contribution because of demographic dynamics unless both labor force participation and unemployment improve significantly. The highway project will contribute to capital accumulation in the near term, but the contribution from capital accumulation will likely fall despite relatively high investment ratios. Based on historical performance, the contribution from TFP is likely limited and constitutes the main bottleneck for long-term growth prospects in the no-reform baseline.